INTERDISCIPLINARY META-LEVEL UNIFICATION SCHEME-INTERPRETATIONISM AND SOME PROBLEMS OF SYSTEMS, MODELS AND INSTRUMENTAL HERMENEUTICS - LENK, HANS (International Journal of Multidisciplinary Research and Studies, 2022)
Overall, the current reality and the scientifically represented world is much more than hitherto characterized by problems of cross-disciplinary or “inter-areal” connections of diverse topical research fields within complex and highly interconnected real, model, and quasi artificial systems. Here, we will address the respected problem of the humanities and social sciences somewhat by the rather old-fashioned contrast to the natural sciences. In the main part, I shall sketch my own approach that I call (scheme-) interpretations or methodological interpretative constructivism. This methodological concept seems to me to make possible a bridge between the disciplines – at least by going higher level in one’s methodology. The next part will turn to the historical and methodological questions of text-interpretations or methodological hermeneutics thus amounting to a prominent special case of the scheme-interpretations approach. Finally, the last part draws some methodological conclusions regarding an abstract interpretation of “reunification” between the different scientific disciplines and everyday understanding.